(untitled) (Northern International Medical College Journal, 2025)
Background: To control over population and improving maternal health, to reduce maternal and child mortality and morbidity, to improve living standards and the quality of life of the people WHO recommended practicing contraceptive methods. Population of Bangladesh is increasing with an alarming rate even there is significant progress in family planning program. Objective: The aim of this study was to determine the prevalence of Oral Contraceptive pill (OCP) use among married women in rural Bangladesh. Methodology: This study was done among married women residing Islampur village in Dhamrai Upazila during October 2021 to March 2022. The cross-sectional type of descriptive study design was followed, and sample size was 200, selected by nonprobability purposive sampling. Data was collected by face-to-face interview using structured questionnaire. The questionnaire was prepared by a researcher and pretested before data collection. Informed consent and ethical clearance obtained from proper authority prior to data collection. All statistical analyses were performed using the SPSS software version 21. Result: In this study 200 married women were selected 47.50% and 30.50% were from 18-28 years and 26-33 years age group respectively. Regarding education 23% completed primary level and 28% completed junior level. Housewife was 78.50% and 55.5% earned taka 15000 – taka 20000 per month. Ninety-nine percent (99%) respondents had the idea about contraceptive method. Regarding contraceptive use in 48.50% cases, the decision was taken by both (husband and wife) and in 32% cases decision was taken by husband alone. Health workers and family members were the main sources of information which was 41% and 40.50% respectively. Most of the respondents (89.76%) had no constraint in using contraceptives. Among the respondents, 83% used contraceptive methods. Among the contraceptive users 68.70% used OCP. The reason for taking OCP 86.85% responses was to keep their family size small. About 50.90% of respondents use oral contraceptive pills (OCP) free of cost and 49.14% respondents collected OCP from pharmacy with 50 taka or more per month. Among the respondents 38.60% experienced no side effects but 61.40% respondents experienced side effects in using oral contraceptive pills. Nausea and severe headache complained by 30.80% and 23.30% respectively. Conclusion: In this study we found that the prevalence of OCP use was satisfactory among the study population. Women were educated up to secondary level but aware about the value of small family that directed them to use OCP. No constraint was found in using OCP. Health workers were the main source of information about cotraceptive. The free supply of OCP got only 50.90% and others collected it from pharmacy with own cost (taka 50 or more). Northern International Medical College Journal Vol. 14 No. 1-2 July 2022-January 2023, Page 619-623